DETERMINAN TINGKAT HUTANG SERTA HUBUNGAN TINGKAT HUTANG TERHADAP NILAI PERUSAHAAN: PERSPEKTIF PECKING ORDER THEORY - Amirya, Mirna; Atmini, Sari (UI Scholars Hub, 2008)
Based on Pecking Order Theory, the objective of this study is to examine the effect of dividend policy, profitability, sales growth, and total assets growth towards financial leverage and the effect of financial leverage as an intervening variable towards firm value. The sampling method is purposive sampling method and there are 33 firms that fulfil the criteria. Data are analyzed using path analysis method. The results show that dividend policy and profitability have negative influence on financial leverage, while total assets growth has positive influence on financial leverage. Financial leverage has negative relation on firm value.